Evaluación de la uniformidad intrínseca en gamma cámaras del servicio de medicina nuclear del Hospital san Juan de Dios - Mora Ramírez, Erick (Universidad de Costa Rica, 2009)
The quality assurance program in a Nuclear Medicine Department aims to minimize errors and artifacts that cover all aspects of clinical practice. The quality control can be seen such as one particular procedure used to meet measurements that can be followed along the time. The intrinsic flood-field uniformity is one of the quality control procedures to evaluate the response of a gamma camera to a spatially uniform flux of an incident gamma radiation over the field of view. The purpose of this study is to test our gamma cameras, recording the integral and differential uniformity figures of the intrinsic uniformity during the 2007 in order to establish how well the instruments were working. At the beginning we perform an evaluation of our acquisition protocol which implies the variation of the acquired counts, the energy window width and its placement. After that we analyze the recording data creating plots which are showing the performance of the systems. Using an energy window placed at 140 keV at 20%, with matrix size of 512 x 512, acquiring 15 million counts and the source activity close to 700 °C; we think that we get a good enough images and both uniformities are within the manufacture's requirements, however, increasing the number of acquired counts, images are much better and an improvement in the evaluated parameters can be seen. The performance evaluation, of the three gamma cameras, was taking into account for approximately 240 days, showing an integral uniformity range of 1.04 ± 3.5 % and the range for differential uniformity vary from 0.88 up to 2.7 %. We conclude that the gamma cameras were working quite well, we do not need to vary our acquisition protocol because it is good enough to perform this test; also factors affecting the quality of the images are radioactive waste material not very well shielded and temperature room variations, especially at the beginning of our workday.